2012
DOI: 10.1111/j.1365-246x.2012.05426.x
|View full text |Cite
|
Sign up to set email alerts
|

Dependency of slab geometry on absolute velocities and conditions for cyclicity: insights from numerical modelling

Abstract: SUMMARY The aim of this study is to quantify the relationship between the kinematics of subduction, deformation in the overriding plate and the evolution of slab geometry. A 2‐D finite element numerical code is used, and a first objective consists in benchmarking previously published analogue models. Far‐field plate velocities are applied, and once the subducting plate reaches the 660 km discontinuity, modelled as a rigid base, we obtain two different forms or styles of subduction that depend on the overriding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(82 citation statements)
references
References 62 publications
(189 reference statements)
7
72
1
Order By: Relevance
“…Slab folding generates variations in time of the subduction dip, changing the state of stresses in the overriding plate and consequently also the surface topography. In 2‐D models, Gibert et al [] and Cerpa et al [] showed that periods of low slab dip generate periods of compression in the overriding plate, consistent with observations in natural subduction zones [ Lallemand et al , ]. In contrast, the OP stretches when the slab sinks before its first contact with the 660 km discontinuity, and during periods of slab rollback.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Slab folding generates variations in time of the subduction dip, changing the state of stresses in the overriding plate and consequently also the surface topography. In 2‐D models, Gibert et al [] and Cerpa et al [] showed that periods of low slab dip generate periods of compression in the overriding plate, consistent with observations in natural subduction zones [ Lallemand et al , ]. In contrast, the OP stretches when the slab sinks before its first contact with the 660 km discontinuity, and during periods of slab rollback.…”
Section: Introductionmentioning
confidence: 57%
“…Gibert et al [] have determined a kinematic condition that predicts slab folding with 2‐D subduction models. If | v op |< v s ( v s = v op + v sp is the subduction velocity when internal overriding plate deformation is neglected), then the subducting plate folds when depositing over the 660 km discontinuity.…”
Section: Mechanical Modeling Numerical Strategy and Model Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…If the overriding plate is fixed, F SU will be larger with respect to the setting with a free overriding plate. Furthermore, the magnitude of F SU_HOR depends on the subduction interface dip angle (α; F SU_HOR = F SU sin(α), see Figure ), which in turn is controlled by the trench velocity (a decrease in trench velocity causes an increase in dip angle) [ Schellart , ; Griffiths et al ., ; Gibert et al ., ]. The value of α in the fixed overriding plate models is larger than that in the free overriding plate models due to a lower trench velocity (Figures a–d and 4).…”
Section: Discussionmentioning
confidence: 94%
“…In the models with fixed overriding plates, the slab developed a recumbent fold after arriving at the bottom of the tank (Figures c and d). This geometric feature can be attributed to the relatively low velocity of the trench (Figures c and d), as suggested in previous works [e.g., Kincaid and Olson , ; Christensen , ; Čížková et al ., ; Schellart , ; Gibert et al ., ; Duarte et al ., ]. A slow trench retreat velocity results in an increase of the slab dip and eventually in an overturned slab.…”
Section: Discussionmentioning
confidence: 97%